A14 GUT-RESIDING BACTERIA CAN SHAPE HOST DRUG METABOLISM IN THE SMALL INTESTINE THROUGH AN INNATE LYMPHOID CELL-IL-22 DRIVEN AXIS. (26th February 2020) - Flannigan, K L; Johnston, M; Erickson, S L; Nieves, K; Jijon, H; Gallo, M; McCoy, K; Hirota, S A
Abstract: Background: The ability of the intestinal microbiota to influence drug metabolism has been recognized, however the mechanisms through which this occurs remain unexplored. Recent work in germ-free mice showed that conventionalization with specific pathogen free (SPF) microbiota influences the expression of cytochrome P450 (CYP) enzymes in the liver and small intestine (SI), two important sites of drug metabolism. Given that CYP enzymes, including CYP3A11 in mice, account for roughly 70% of total drug metabolism, we hypothesized that commensal gut bacteria can shape the CYP landscape to influence drug metabolism and therapeutic outcomes. Aims: To investigate the role of specific gut-residing microbes in shaping the expression and activity of host drug metabolism enzymes. Methods: Segmented filamentous bacteria (SFB)-free mice were obtained from Jackson Lab (Jax) and colonized with feces from SFB-mono-associated mice via oral gavage. 14 days later, expression of drug metabolism enzymes in the SI were probed using PCR arrays, and lamina propria cells isolated for flow cytometry. A monoclonal antibody for Thy1.2 was used to deplete innate lymphoid cells (ILCs) in RAG1 -/- mice (lacking T- and B-cells). CYP3A11 activity was determined through the colorimetric breakdown of the CYP3A11-specific substrate 7-benzyloxyresorufin. SI organoids were generated from mice and humans, and treated with IL-22 to further assess the dynamics of CYP3A11/CYP3A4 expression and activity. Results: Colonization of Jax mice with immunomodulatory SFB altered the expression of various CYP enzymes in the SI (but not liver), with Cyp3a11 being the most downregulated gene. Further analysis showed that SFB-induced IL-22 production by type 3 ILCs (ILC3) correlated with reduced SI Cyp3a11 expression. Additionally, SFB colonization had no effect on the expression of Cyp3a11 in the SI of mice in which ILCs were depleted. Both SFB colonization and administration of IL-23, to induce IL-22 from ILC3, increased the ability of the CYP3A11-metabolized drug glyburide to decrease blood glucose levels when given orally. In mouse SI enteroid cultures, IL-22 dose-dependently reduced the expression of Cyp3a11 and decreased the ability of enteroids to metabolize CYP3A11-specific substrates. Finally, IL-22 induced wide changes in the transcriptome of human SI enteroids, with substantial effects on a drug metabolism pathway centred around CYP3A. Conclusions: Our data suggest that a gut-resident microbe (SFB) can influence the expression and activity of the drug metabolising enzyme CYP3A11 in the SI through an ILC3-IL-22 dependent mechanism. These findings provide an understanding of how the intestinal microbiota may modulate host drug metabolism to influence the efficacy and toxicity of various pharmaceutical compounds. Funding Agencies: CAG, CIHRAbbvie, Lloyd Sutherland Investigatorship